2017
DOI: 10.1590/s1679-45082017ao3936
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the dipstick screening test as a predictor of negative urine culture

Abstract: Objective To investigate whether the urine dipstick screening test can be used to predict urine culture results.Methods A retrospective study conducted between January and December 2014 based on data from 8,587 patients with a medical order for urine dipstick test, urine sediment analysis and urine culture. Sensitivity, specificity, positive and negative predictive values were determined and ROC curve analysis was performed.Results The percentage of positive cultures was 17.5%. Nitrite had 28% sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
5
12
1
11
Order By: Relevance
“…A statistically significant difference was found between dipstick and microscopic analysis of urine regarding urinary tract infection(leucocytes and or nitrate) as 67% of cases who were +ve for urinary tract infection by dipstick, were +ve for pus by microscopic analysis with p-value 0.003 (table 3) which also in agreement with our study. (19) Also, Marques et al 2017 reported that 28% of cases who had positivity to nitrite and 79% of positive cases to leucocytes esterase by dipstick had confirmed with microscopic examination (19) which were higher slightly than the results of the present study as no cases of positive nitrate by dipstick was positive for pus cells by microscopic examination ,while 33.3% of cases who were positive to leucocytes esterase in dipstick test showed pus cells in microscopic examination (table 3).…”
Section: Discussioncontrasting
confidence: 51%
“…A statistically significant difference was found between dipstick and microscopic analysis of urine regarding urinary tract infection(leucocytes and or nitrate) as 67% of cases who were +ve for urinary tract infection by dipstick, were +ve for pus by microscopic analysis with p-value 0.003 (table 3) which also in agreement with our study. (19) Also, Marques et al 2017 reported that 28% of cases who had positivity to nitrite and 79% of positive cases to leucocytes esterase by dipstick had confirmed with microscopic examination (19) which were higher slightly than the results of the present study as no cases of positive nitrate by dipstick was positive for pus cells by microscopic examination ,while 33.3% of cases who were positive to leucocytes esterase in dipstick test showed pus cells in microscopic examination (table 3).…”
Section: Discussioncontrasting
confidence: 51%
“…Já em relação aos CGP, o S. aureus foi o único com a presença de nitrito em 0,7% (3) (9) em Maringá-PR, onde a frequência de ITU foi de 86,6% (388/448; IC 95%: 83,0-89,6) para BGN e de 13,4% (60/448; IC 95%: 10,[5][6][7][8][9][10][11][12][13][14][15][16]9) para CGP, sendo que as amostras analisadas foram da primeira urina da manhã, através da técnica do jato médio de micção espontânea, semelhante à amostragem do nosso estudo.…”
Section: Methodsunclassified
“…Esses são considerados possíveis indicadores de infecção urinária causada por bactérias. (9,10) O nitrito urinário é um produto da conversão de nitrato a nitrito por algumas bactérias, principalmente os BGN. Este é detectado pela reação de Greiss, sendo que o nitrito em pH ácido reage com a amina aromática para posterior formação de um composto diazônico, reagindo com compostos tetrahidrobenzoquinolina, produzindo um diazo róseo.…”
Section: Introductionunclassified
See 2 more Smart Citations